CHARACTERIZATION WITH DISSOCIATIVE IDENTITY DISORDER IN LOOK AWAY MOVIE - Junaid, Syahruni; Darmadali, Waode Surya; Ningsih, Suci Hartika (Journal of Islamic Culture and Literature (JICeL), 2023)
This research disscussed Dissociative Identity Disorder in Look Away Movie. Which aimed to find out the symptoms and the causes of Dissociative Identity Disorder the main character. This research used Joseph M.Bogs theory of characterization and Thomas Oldmands theory of Dissociative Identity Disorder with descriptive qualitative method and note taking as an instrument. This research was conducted in order to enhance and enrich the knowledge of the readers about the importance of dissociative identity disorder. The finding showed dissociatvie identity disorder started from family, a child who experienced this case due to parents demands or parent attitude that was so hard on them. In addition, suggestions from people around are also the cause of this. They create other personalities so that they can be accepted by the people around them. Therefore, the role of parents is needed in the formation of a child’s personality. They went acceptance, affection, and attention from their parents.